I speak for myself American women on being Muslim - Ebrahimji, Maria M.; Suratwala, Zahra T. (I speak for myself series, 2011)
Forty women under age forty share what it has been like to have been born and raised in the United States as a Muslim, examining the dichotomy between Islamic and Western values, and discussing stereotypes, the events of 9/11, and other related topics.